A novel point-of-care testing strategy for sexually transmitted infections among pregnant women in high-burden settings: results of a feasibility study in Papua New Guinea. Issue 1 (December 2016) - Badman, Steven; Vallely, Lisa; Toliman, Pamela; Kariwiga, Grace; Lote, Bomesina; Pomat, William; Holmer, Caroline; Guy, Rebecca; Luchters, Stanley; Morgan, Chris; Garland, Suzanne; Tabrizi, Sepehr; et al.
Abstract Background Sexually transmitted and genital infections in pregnancy are associated with an increased risk of adverse maternal and neonatal health outcomes. High prevalences of sexually transmitted infections have been identified among antenatal attenders in Papua New Guinea. Papua New Guinea has amongst the highest neonatal mortality rates worldwide, with preterm birth and low birth weight major contributors to neonatal mortality. The overall aim of our study was to determine if a novel point-of-care testing and treatment strategy for the sexually transmitted and genital infectionsChlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Trichomonas vaginalis (TV) and Bacterial vaginosis (BV) in pregnancy is feasible in the high-burden, low-income setting of Papua New Guinea. Methods Women attending their first antenatal clinic visit were invited to participate. CT/NG and TV were tested using the GeneXpert platform (Cepheid, USA), and BV tested using BVBlue (Gryphus Diagnostics, USA). Participants received same-day test results and antibiotic treatment as indicated. Routine antenatal care including HIV and syphilis screening were provided. Results Point-of-care testing was provided to 125/222 (56 %) of women attending routine antenatal care during the three-month study period. Among the 125 women enrolled, the prevalence of CT was 20.0 %; NG, 11.2 %; TV, 37.6 %; and BV, 17.6 %. Over half (67/125, 53.6 %) of women had one or more of these infections. Most women were asymptomatic (71.6 %; 47/67). Women aged 24 years and under were more likely to have one or more STI compared with older women (odds ratio 2.38; 95 % CI: 1.09, 5.21). Most women with an STI received treatment on the same day (83.6 %; 56/67). HIV prevalence was 1.6 % and active syphilis 4.0 %. Conclusion Point-of-care STI testing and treatment using a combination of novel, newly-available assays was feasible during routine antenatal care in this setting. This strategy has not previously been evaluated in any setting and offers the potential to transform STI management in pregnancy and to prevent their associated adverse health outcomes.